Preventing Injuries in Workers: The Role of Management Practices in Decreasing Injuries Reporting - Fariba Kiani; Mohammad Reza Khodabakhsh (Kerman University of Medical Sciences, 2014)
Background Researchers have found that management safety practices may predict occupational injuries and psychological distresses in the workplace. The present study examined the perception of management safety practices related to injuries reporting and its dimensions among workers of Isfahan Steel Company (ESCO). Methods A self-administered anonymous survey was distributed to 189 workers. The survey included demographic factors, management safety perception, injuries reporting and its components (physical symptoms, psychological symptoms, and injuries). The data were analyzed by Multivariate and correlation techniques. Results The results showed that: 1) there were significant correlations between management safety perception with injuries reporting and its two dimensions namely physical and psychological symptoms; 2) there was no significant relationship between management safety perception and injury; 3) in Multivariate analysis, management safety perception significantly predicted about 26%, 19%, and 28% of the variances of variables of injuries reporting, physical symptoms, and psychological symptoms respectively (P< 0.01). Conclusion Improving employees' perception of management safety practices can be important to prevent the development of job injuries and to promote workers' safety and well-being.